PENGELOLAAN SAMPAH DI KAWASAN WISATA ALAM PUREKMAS SESAOT KABUPATEN LOMBOK BARAT - Susmaini Ana; Endah Wahyuningsih; Diah Permata Sari (Universitas Lambung Mangkurat, 2024)
Zero waste is the flagship program of the Governor of NTB for the 2018-2023 period. This zero waste activity is an agenda to improve the environmental conditions of the community implemented by the Regency government. For research purposes, analyzing waste generation in the Purekmas Sesaot Nature Tourism Area and analyzing waste management in the Purekmas Sesaot Nature Tourism Area. This research uses qualitative and quantitative descriptive methods, with the collection method referring to SNI 19-396-1994 concerning Methods of Taking and Measuring Examples of Waste Generation and Composition. For waste management using a questionnaire that is analyzed using a Likert scale. The results of this study show that waste generation for 8 consecutive days amounted to 310.22 kg from the overall component. Waste management in the Purekmas Sesaot Nature Tourism Area for types of waste that have no selling value, the waste is managed by burning, stockpiling and letting it accumulate because until now there has been no TPS and TPA in the Purekmas Sesaot Nature Tourism Area.